A Study of Prevalence of Lipid Abnormalities in HIV Infected Children among Indian Population - Rakesh Gupta; Amit Pathania; Archana Gupta; Nikhilesh Kumar; SK Jatana (HIV/AIDS Research and Treatment-Open Journal, 2015)
Introduction: With the universal availability of Highly active antiretroviral therapy (HAART), HIV is increasingly recognized as a chronic manageable disease, rather than terminal illness. However the cost of increased longevity has resulted in to various metabolic abnormalities, mainly lipids. These metabolic abnormalities could be due to the HIV disease itself or due to the effects of antiretroviral therapy. Data on the prevalence of these metabolic abnormalities particularly in the pediatric population is limited, hence this study was conducted to find out the prevalence of lipid abnormalities in HIV infected children among the Indian population. Materials & Methods: This was a cross-sectional study conducted at Pediatric HIV clinic of a tertiary care hospital in western state of India from Sep 2010 to Aug 2012 among HIV infected children up to 18 years of age. After taking detail history and examination, fasting samples were taken for complete lipid profile. All enrolled HIV positive children were categorized according to clinical and immunological status as per WHO guidelines of 2010. The lipid abnormalities in HIV infected children on antiretroviral therapy & not on antiretroviral therapy were analysed. Statistical analysis was done by Z test for continuous variables and chi square test for dichotomous variables using Graph pad Prism 5 software. Results: 140 HIV positive children were enrolled, of which 93 were on ART. Mean age of the study population was 8.8 years with male to female ratio of 1.1:1. The mode of HIV transmission was vertical in 137(97.8%) children. WHO clinical categories at the time of enrolment were cat I, II, III and IV in 40%, 39%, 20% and 1%, while immune cat 42%, 18%, 16% and 24% cases respectively. Ninety three (64%) children were on antiretroviral therapy. Of the total, 80(57%) children were found to have lipid abnormalities, of which most common was high triglycerides levels in 74(52.8%) children followed by low HDL in 64(46%), high cholesterol in 19(13.5%) and high LDL in 3(2%) children. Mean levels of cholesterol, triglycerides and LDL were higher in the ART group at 156, 126, 50 and 56 mg/dl as compared to ART naive group with levels of 129, 119, 39 and 50 respectively and the association between the mean levels of cholesterol and ART was statistically significant (P value=0.0002). Conclusion: The prevalence of lipid abnormalities was higher in HIV infected children, mainly triglycerides and cholesterol. Also the prevalence was higher in HIV infected children on ART as compared to ART naïve children. These metabolic abnormalities may contribute to the in creased risk of cardiovascular diseases in these children, who are likely to be facing a life time exposure to antiretroviral therapy, hence regular screening is recommended to identify and manage the abnormalities early.